Effective implementation of the balanced scorecard in the Sarawak Public Sector: a case study on Sarawak State Treasury Department - Sharifah Rodziah, Binti Sayeed Aman Ghazali (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This paper aims to examine the use of the balanced scorecard (BSC) as a performance management tool in the Sarawak public sector, drawing on the Sarawak State Treasury Department as a case study. It seeks to identify issues and challenges, critical success factor, impact on the agency in implementing the BSC and the linkage between Corporate Governance. Content Analysis and the MAXQDA J J software are being utilised to analyse the research data) The data are from two sources, the interviews and JPNS's records and documentation on the agency's BSC. The findings reveal perceived BSC utility as performance measurement, reporting and performance management role. This study identifies users' perceptions of the key challenges, critical success factors, impact on the agency's performance and service delivery, benefits of BSC and highlights their significance for both practice and theory. It adds to prior studies by specifically examining the factors that support and impede the effective implementation ofthe BSC in public sector contexts. BSC had made the agency as a strategy focus organisation driven by the top management support and commitment, effective communication, system support and comprehensive quality structure which saw improvement in performance and effective service delivery.